Early cardiotoxicity after adjuvant concomitant treatment with radiotherapy and trastuzumab in patients with breast cancer - Marinko, Tanja (Radiology and oncology (Ljubljana), 2018)
The purpose of the study was to find out whether there is a difference in the early parameters of cardiotoxicity (left ventricular ejection fraction LVEF and N-terminal pro-B-type natriuretic peptide NT-proBNP) between the two groups of patients: the patients treated for left breast cancer (left breast cancer group) and those treated for the right breast cancer (right breast cancer group), after the treatment had been completed. Patients and methods. The study included 175 consecutive patients with human epidermal growth factor receptor- 2 (HER2) positive early breast cancer, treated concurrently with trastuzumab and radiotherapy (RT), between June 2005 and December 2010. Echocardiography with LVEF was performed before adjuvant RT (LVEF0) and in all patients after the concurrent treatment had been completed (LVEF1) as well as we carried out the NT-proBNP measurements. The difference (%) between LVEF0 and LVEF1 was analysed (% LVEF = LVEF0 - LVEF1) and compared between the two groups. Results. There were 84 patients in the left and 91 in the right breast cancer group. Median observation time was 57 (37%71) months. Mean % LVEF (%) was -1.786% in the left and -2.607% in the right breast cancer group (p = 0.562, CI: -2.004 to 3.648). Median NT-proBNP were 111.0 ng/l in the left and 90.0 ng/l in the right breast cancer group (p = 0.545). Echocardiography showed that the patients in the left breast cancer group did not have significantly worse systolic and diastolic left ventricular function in comparison with the patients in the right breast cancer group, but, they had higher incidence of pericardial effusion (9 11% vs. 1 1%) (p = 0.007). Conclusions. We did not find any significant differences in the early parameters of cardiotoxicity (LVEF, NT-proBNP) between the two groups we observed. Those patients who were irradiated on the left breast/chest wall had higher incidence of pericardial effusion.
Keywords: adjuvant radiotherapy; breast cancer; cardiotoxicity; dopolnilna radioterapija; kardiotoksičnost; radioterapija; radiotherapy; rak dojke